2010
DOI: 10.4314/nifoj.v25i2.50841
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition of cowpeas infested with Callosobruchus Maculatus L. in Zaria.

Abstract: Nutrient composition of cowpeas infested withCallosobruchus Maculatus L. in Zaria.Cowpeas infested with Callosobruchus maculatus, in Zaria were analysed using standard biochemical methods.The analysis was to determine the effect of Callosobruchus maculatus on cowpeas at various stages of infestation. Four varieties "Kannanado", Local brown, "Dan Borno" and IAR-48 were used. Results show significant decrease in moisture with increase in infestation in all the varieties except for 'Kannanado', this was also the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
5
4
0
Order By: Relevance
“…Also, there is insignificant effect of PP and LD packing on protein content. The results are similar to the studies conducted by Mbah and Silas (2007) which reported an increase in protein contents with severity of infestation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Also, there is insignificant effect of PP and LD packing on protein content. The results are similar to the studies conducted by Mbah and Silas (2007) which reported an increase in protein contents with severity of infestation.…”
Section: Resultssupporting
confidence: 91%
“…It was further observed there was little increase of true constituents in the treated samples also, which may be due to hidden infestation. A similar trend was observed by Hamdi et al (2017), Bamaiyi et al (2006) and Mbah and Silas (2007) that protein, moisture and ash contents increased in infested seeds of cowpea. Thermal treatment (T 5 ) i.e.…”
Section: Resultssupporting
confidence: 88%
“…The chemical composition of dry common bean seeds infested with A. obtectus showed an increase in protein and fibre contents and a decrease in moisture, carbohydrate and fat contents for all varieties. This was in agreement with the findings of MBAH & SILAS (2007), who reported an increase in protein in cowpeas infested with Callosobruchus maculatus (FABRICIUS, 1775). The increase may be attributed to the presence of the pest's eggs, egg cases and excreta.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the reduction in fat and carbohydrate contents was not solely dependent upon the development of progeny but depended on other factors, including varietal resistance and insect preference. It has been reported that storage pests cause considerable quantitative as well as qualitative losses, ultimately leading to a deterioration in nutritional value (NEETHIRAJAN et al 2007); in addition, the decrease in moisture content obtained in this study may be linked to the metabolic activities of seeds (MBAH & SILAS 2007). Generally, changes in the chemical composition of dry common bean seeds infested with A. obtectus were inconsistent, with increases in some of the nutritional components (protein and fibre contents) and decreases in others (moisture, carbohydrate and fat contents).…”
Section: Discussionmentioning
confidence: 52%
“…Most often the seeds and pods of cowpea are boiled and eaten as vegetable or are consumed after cooking to provide protein and several vitamins and minerals while the leaves or stems serve as fodder for livestock feeding. In Nigeria, cowpea is consumed in the form of bean pudding, bean cake, baked beans, fried beans, bean soup among others (Mbah and Silas, 2007). High protein contents and lysine contents make cowpea a natural supplement to staple diets of cereals, roots and tubers commonly grown in many poor countries (Adekola and Oluleye, 2007).…”
Section: Introductionmentioning
confidence: 99%